BASED ON AVERAGING METHOD ANALYSIS OF THE SINGLE DEGREE OF FREEDOM AMPLITUDE FREQUENCY - WANG ShuGuo; GUO LiFeng; LIAO PengTai; ZHANG YanBo (Jixie qiangdu)
Improved averaging method was used to receive the vibration differential equation of the approximate solution, and the amplitude frequency response equation was obtained. By employing an averaging method, the transition boundary was calculated. The types of the amplitude-frequency responses were analyzed; secondly, the functions were also used for stability analysis by the linear system theory. Finally, the vibration isolation effect of different parameters on the system are analyzed. Increasing damping ratio weakened the vibration of the system, and strengthened the effect of vibration isolation.